Pengaruh Tingkat Gejala Kecemasan terhadap Indeks Prestasi Akademik pada Mahasiswa Angkatan 2016 Fakultas Kedokteran Universitas Muhammadiyah Sumatera Utara - Hasibuan, Siti M.; Riyandi, Rian (Jurnal Biomedik : JBM, 2019)
Abstract: Medical students have different levels of stress and anxiety, albeit, those levels are relatively high due to their important roles in the field of study. High levels of anxiety were found among the first year medical students. In Indonesia, the number of anxiety increases each year. It is estimated that 20% of world population suffer from anxiety; 47.7% were teenagers. This study was aimed to obtain the relationship between the levels of anxiety symptom and the academic performance index among students of batch 2016 at the Faculty of Medicine, University of Muhammadiyah Sumatera Utara. This was a descriptive analytical study with a cross sectional design. The results showed several levels of anxiety symptoms, as follows: mild anxiety symptoms (32.7%), moderate anxiety symptoms (29.8%), severe anxiety symptoms (6.7%), and very severe anxiety symptoms (5.8%); 25% of students had no anxiety symptoms. The Kruskal-Wallis analysis obtained the p-value of 0.005 which meant there was an influence of the level of anxiety symptoms on the academic performance index. In conclusion, levels of anxiety symptoms could influence the academic performance index among students of batch 2016 at the Faculty of Medicine, University of Muhammadiyah Sumatera Utara.Keywords: anxiety symptoms, academic performance index, medical studentsAbstrak: Mahasiswa Fakultas Kedokteran memiliki tingkat stres dan kecemasan yang berbeda-beda tetapi akan relatif tinggi karena peran penting di bidang yang mereka geluti. Umumnya tingkat kecemasan tinggi ditemukan pada mahasiswa kedokteran tahun pertama. Di Indonesia setiap tahun jumlah kecemasan meningkat. Diperkirakan 20% dari populasi dunia dan sebanyak 47,7% remaja mengalami kecemasan. Penelitian ini bertujuan untuk mengetahui hubungan antara tingkat gejala kecemasan dengan indeks prestasi akademik pada mahasiswa Fakultas Kedokteran Universitas Muhammadiyah Sumatera Utara (FK UMSU) angkatan 2016. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Hasil penelitian memperlihatkan mahasiswa paling banyak mengalami tingkat gejala kecemasan ringan (32,7%), diikuti oleh gejala kecemasan sedang (29,8%), normal (25%), gejala kecemasan berat (6,7%), dan gejala kecemasan berat sekali (5,8%). Analisis uji Kruskal-Wallis memperoleh nilai p=0,005 yang menunjukkan adanya pengaruh tingkat gejala kecemasan pada indeks prestasi akademik. Simpulan penelitian ini ialah terdapat pengaruh tingkat gejala kecemasan terhadap indeks prestasi akademik pada mahasiswa angkatan 2016 di Fakultas Kedokteran Universitas Muhammadiyah Sumatera Utara.Kata kunci: gejala kecemasan, indeks prestasi akademik, mahasiswa kedokteran